2021
DOI: 10.1186/s12889-021-10218-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality and readability of web-based Arabic health information on COVID-19: an infodemiological study

Abstract: Background This study sought to assess the quality and readability of web-based Arabic health information on COVID-19. Methods Three search engines were searched on 13 April 2020 for specific Arabic terms on COVID-19. The first 100 consecutive websites from each engine were analyzed for eligibility, which resulted in a sample of 36 websites. These websites were subjected to quality assessments using the Journal of the American Medical Association (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 30 publications
8
22
0
Order By: Relevance
“…A slight majority (64%) of European countries were found to have written online COVID-19 material available in alternative languages; a mere 48% – including the Netherlands – had materials available in at least one of the three most common migrant languages of the country [26] . Furthermore, the readability of online COVID-19 content is often too difficult to understand [ 17 , 27 , 28 ]. Our study indicates meeting language and literacy needs is paramount to improve uptake of preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…A slight majority (64%) of European countries were found to have written online COVID-19 material available in alternative languages; a mere 48% – including the Netherlands – had materials available in at least one of the three most common migrant languages of the country [26] . Furthermore, the readability of online COVID-19 content is often too difficult to understand [ 17 , 27 , 28 ]. Our study indicates meeting language and literacy needs is paramount to improve uptake of preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published analyses on the reliability and accuracy of online health information mainly focus on otorhinolaryngology-related topics [23][24][25][26][27][28][29][30]. Studies on other medical conditions, such as idiopathic pulmonary fibrosis, SARS-CoV-2, neurological disorders, etc., are available as well [15,[31][32][33][34][35][36]. However, except for oral precancerous conditions, other precancerous and cancer entities were not in the focus of such evaluations [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results are in line with these previously published studies. Those conclude on frequently outdated, mixed-, or low-quality, and incomplete online health information that requires high readability skills [15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies [ 34 , 52 , 53 ] have shown that some public health agencies have also failed to provide information in an easy-to-read form. Valizadeh-Haghi et al [ 52 ] examined the readability of English-language COVID-19 information based on website categories (ie, news, governmental, commercial, organization, educational) and concluded that that the readability levels in all categories exceeded the recommended level and that commercial websites had better readability than governmental websites.…”
Section: Discussionmentioning
confidence: 99%
“…Mishra et al [ 34 ] reported that the readability of English-language COVID-19 information on 18 government and international public health agency websites did not meet the recommended readability level. Halboub et al [ 53 ] investigated 36 Arabic-language websites on COVID-19 and reported that 66.7% of the included websites were easy for the general public to read. Kruse et al [ 33 ] conducted a study of COVID-19 information provided by 8 US academic medical centers and reported that 0.7% of information was written at or below the sixth-grade level.…”
Section: Discussionmentioning
confidence: 99%